Estrategias comunicativas del Movimiento Alianza País en el Ecuador 2008 - 2011 - Ruiz Velásquez, Marco Xavier (2013)
The Communication is the process by which human interaction becomes possible. It´s broad impact on human life makes possible the cultural, social and human manifestation, and the way human being relates to the universe and it´s environment. Communication has a diversified field that determines structures in the social order, that´s why their study must be done from the parts that make up these structures. In this research´s work we will analyze the communication in its political arena, thus field makes a condition between state representatives and citizenship relationship. In this sense, the meaning of this research is intended to study, understand and analyze political communication in a context has been important in Ecuadorian society.